2014
DOI: 10.1073/pnas.1401887111
|View full text |Cite
|
Sign up to set email alerts
|

Single bacterial strain capable of significant contribution to carbon cycling in the surface ocean

Abstract: Marine dissolved organic carbon (DOC) encompasses one of the largest reservoirs of carbon on Earth. Heterotrophic bacteria are the primary biotic force regulating the fate of this material, yet the capacity of individual strains to significantly contribute to carbon cycling is unknown. Here we quantified the ability of a single Alteromonas strain [Alteromonas sp. strain Scripps Institution of Oceanography (AltSIO)] to drawdown ambient DOC in a coastal ecosystem. In three experiments, AltSIO alone consumed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
202
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(223 citation statements)
references
References 61 publications
18
202
2
1
Order By: Relevance
“…This may be attributable to the fact that reduced resource diversity and variable supply, as typical for highaltitudinal streams (Battin et al, 2004;Milner et al, 2009), may prevent microorganisms from specialising on a few carbon sources. This observation is in line with recent reports on marine microorganisms showing a low degree of specialisation on carbon sources (Mou et al, 2008;Pedler et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…This may be attributable to the fact that reduced resource diversity and variable supply, as typical for highaltitudinal streams (Battin et al, 2004;Milner et al, 2009), may prevent microorganisms from specialising on a few carbon sources. This observation is in line with recent reports on marine microorganisms showing a low degree of specialisation on carbon sources (Mou et al, 2008;Pedler et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…The strength of the effect, represented by the critical density, increased with predation and decreasing carbon ( figure 1). Possibly, even more pronounced Allee effects would be observed in natural marine populations of heterotrophic bacteria where natural concentrations of dissolved organic carbon are up to three orders of magnitude lower than in our experiments [14]. V. fischeri populations subject to C. roenbergensis predation at natural concentrations [15] had a significantly higher critical threshold than populations without predation.…”
Section: Discussioncontrasting
confidence: 52%
“…Alteromonas are typically not very common in the oceans (Eilers et al, 2000) yet are often identified in rRNA-based analyses of microbial communities in open water, and thus naturally co-occur with Prochlorococcus (García- Martínez et al, 2002;Ivars-Martinez et al, 2008;Lopez-Perez et al, 2012). They are metabolically-versatile copiotrophs (Pedler et al, 2014), rapidly responding to increases in dissolved organic matter and often dominating mesocosm experiments (McCarren et al, 2010). Several Alteromonas strains have been shown to inhibit eukaryotic phytoplankton such as diatoms, dinoflagellates and raphidophytes (reviewed by Mayali and Azam, 2004).…”
Section: Introductionmentioning
confidence: 99%